Trends in Private Sector Development in World Bank Education Projects - Sosale, Shobhana (World Bank, Washington, DC, 2014)
Emerging trends in education show the private sector to be playing an increasingly important role in financing and providing educational services in many countries. Private sector development has not arisen primarily through public policy design, but has of course been affected by the design, and limitations of public policy. The author traces trends in private sector development in eleven of seventy World Bank education projects in 1995-97, asking two questions: What has been the rationale for Bank lending in education? And, in countries where there is both privately financed, and publicly financed, and provided education, how has the Bank encouraged the private sector to thrive? The eleven country samples reveal that the Bank's interest in private sector development is basically in capacity-oriented privatization, to absorb excess demand for education. This is crucial to the Bank's general strategy for education lending: promoting access with equity, focusing on efficiency in resource allocation, promoting quality, and supporting capacity building. Absorbing excess demand tends to involve poorer families, usually much poorer than those that take advantage of other forms of privatized education. The Bank emphasizes capacity-oriented privatization, especially of teacher training for primary, and secondary schools, as well as institutional capacity building for tertiary, and vocational education. The underlying principle is that strengthening the private sector's role in non-compulsory education over time, will release public resources for the compulsory (primary) level. The private sector is emerging as a force governments, donors, and other technical assistance agencies cannot ignore. Often the term private sector encompasses households' out-of-pocket expenses, rather than describing for-profit, or not-for-profit (religious or otherwise) sectors. And lumpy investments, supporting both private, and public education, are the norm.